Estágio: eixo articulador da formação inicial de professores para os primeiros anos da educação básica - Lazzarin, Sandra Regina (2011)
The purpose of the present research is to provide elements to consider a new way to focus teacher training and to contribute with its resignification in Education courses. The study highlights aspects of the Program Bolsa Formação , which was implemented by Secretaria de Educação do Estado de São Paulo and might help reach the referred objective. Based on the methodology of qualitative approach through questionnaire and interview, the field research involved two groups of subjects for investigation: Education college students who act as student researchers in the Program Bolsa Formação and state public school regular teachers. The data were collected in one of the areas of a Diretoria Regional de Ensino located in eastern São Paulo city. The collected data were submitted to analysis and are part of the present study. In the first chapter, the student researcher is introduced to the context of the Program, as well as the other professionals who directly follow the student. The second chapter is focused on teacher initial education and the approach to school practice. In the third chapter, there is a discussion on the knowledge that is built by teachers who are involved in initial education training. In the fourth chapter, the training period is considered as a possibility of joining the teachers to basic schools based on specific educational politics. The fifth chapter brings the present thesis methodological procedures. In the sixth and seventh chapters, the collected data are analyzed and the field research results are presented. In the eighth chapter, some elements are pointed for the development of teacher education courses based on its resignification. Finally, the final considerations are presented in order to contribute to the continuity of the discussion on teacher initial education for the first years of basic school